Revitalizing Hospitality, Managerial, and English for Tourism Purposes Skills: Community Partnership Program for Hotel Employees in Merauke Regency - Lastika Ary Prihandoko; Ana Shohibul Manshur Al Ahmad; Fredy; Fathu Rahman (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The COVID-19 crisis has negatively impacted almost all sectors, including tourism groups in the Merauke Regency area, especially the hotel sector. Hotels face several problem areas in the Merauke area, including in the managerial, technical, and English fields. The Community Partnership Program (PKM) is carried out with the aim of providing knowledge, insight, and abilities for the participants, namely employees of the Sunnyday Inn hotel in Merauke Regency. The implementation of PKM involves experts from community, private, and government organizations to provide training materials to participants. The chairman delivered the managerial competence material of the Merauke branch of the Indonesian Hotel and Restaurant Association. Then, the technical competence material was delivered by the Swissbell Merauke hotel manager. Furthermore, English materials for tourism were delivered by academics. The PKM implementation results are expected to equip hotel employees to be better able to adapt, be creative, and have the agility to the challenges faced during the COVID-19 pandemic so that hotel business activities can quickly recover in the new normal era and the post-pandemic era.